Plan de mejora de la productividad de los procesos de una plataforma de cobranzas de la compañía telefónica Gestión de Servicios Compartidos - Ninapaytan Gomez Arevalillo, Angel R. (2010)
Union Telecom is a Telecommunications project, offering long distance services nationally and internationally that allows users to make calls from the US and Canada to any country, this is contracted by the group of Telefonica del Peru. This company has a billing department, which has a collection method called sectorization, based on the distribution database for each collection agent at random, this makes the call agents according to their convenience to reach their own goals no matter the treatment, and not according to customer behavior, this situation has generated a climate of dissatisfaction for both customers and agents, reflected in high rates of resignations in the service and poor collectibility. As an engineer I could not be based on perceptions, so I used industrial engineering tools to collect information, calling it preliminary audit, where we got the information to know that the problem was the database distribution of sectorization, however the current software was not able to redistribute the database according to the requirement, so we decided to implement a new enterprise software with the ability to not only distribute the database, but other long-term benefits. After a detailed feasibility study, it was decided to implement it. After two months, we undertook a second audit for the comparison with the first one having a conclusion, where we got better results after the implementation of enterprise software.